MyTREEvolution Integrated CSR for a Greener UMP - Siti Sarah, Mohamad Rajimi (2018)
Pekan, 24 February – 300 sapling were successfully planted at Laman Cendekia here in UMP Pekan Campus under the myTREEvolution Integrated CSR Programme organized by Industry Relation Division, Ministry of Higher Education in collaboration with Universiti Malaysia Pahang.